Financial risk management via evaluating impacts of a six factor model on hoi an tourist holding company stock price and transparency disclosure– a case in tourism industry in Vietnam - THANG, DR. TRAN DUC; HUY, DINH TRAN NGOC; MASTER, LE THI HAN; THACH, DR. NGUYEN NGOC (The journal of contemporary issues in business and government, 2021)
Quang Nam tourism industry recently also affected by Covid 19 and Hoi An Tourism Holding Company (HOT) is one of leader with 15% average growth annually. HOT is much paying attention to social security and create more jobs for local laborers. With the use of qualitative and quantitative analysis in OLS model, we get the results presenting that: stock price of HOT (Hoi An company) is much affected by GDP growth and CPI, negative correlation. We can propose suitable policies for better managing company stock price volatility and expan our research for other markets.